A 6-year experience of CPR outcomes in an emergency department in Thailand - Sittichanbuncha Y; Prachanukool T; Sawanyawisuth K (Dove Medical Press, 2013)
Yuwares Sittichanbuncha,1 Thidathit Prachanukool,1 Kittisak Sawanyawisuth2,31Emergency Medicine Department, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 3Research and Diagnostic Center for Emerging Infectious Diseases, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandPurpose: Sudden cardiac arrest is a common emergency condition found in the emergency department of the hospital. The survival rate of out-of-hospital cardiac arrest patients is 2.0%–10.0% and 7.4%–27.0% percent for in-hospital cardiac arrest patients. The factors for survival outcome are divided into three main groups: patient characteristics, pre-hospital factors, and resuscitated information. The objective of this study was to evaluate the related factors, outcome, and survival rate in patients with cardiac arrest who received cardiopulmonary resuscitation (CPR) at Ramathibodi Emergency Medicine Department. There are limited data for this issue in Thailand and other Asian countries.Methods: This retrospective study included all patients who were older than 15 years with sudden cardiac arrest and who were resuscitated in the emergency room between January 2005 and December 2010. Descriptive analytic statistics and logistic regressions were used to analyze factors that related to the sustained return of spontaneous circulation (ROSC) and survival at discharge.Results: There were 181 patients enrolled. The overall sustained ROSC rate was 34.8% and the survival rate at discharge was 11.1%. There were 145 out-of-hospital cardiac arrest patients, in whom the survival rate was 52.4% and the survival to discharge rate was 7.6%. For in-hospital cardiac arrest, there were 36 patients with a survival rate of 86.1% and the survival to discharge rate was 25.0%. Statistically significant factors related to sustained ROSC were good and moderate cerebral performance, in-hospital cardiac arrest, beginning of CPR in less than 30 minutes, and cardiopulmonary cause of arrest. The factors influencing survival to discharge were cardiopulmonary causes of cardiac arrest.Conclusion: Factors associated with sustained ROSC were functional status before cardiac arrest, location of cardiac arrest, duration of CPR, and cause of cardiac arrest. Survival rate was related to the cause of cardiac arrest.Keywords: CPR, cardiac arrest, predictors, emergency department